Pharmacy Response to the Boston Marathon Bombings at a Tertiary Academic Medical Center. (August 2014) - Sylvester, Katelyn W.; Rocchio, Megan A.; Belisle, Caryn; Matta, Lina; Goralnick, Eric
Objective: Effective crisis response requires multidisciplinary communication and rapid action. Our goals are to highlight the experience of a pharmacy department's response to the 2013 Boston Marathon bombing, to discuss the role of the pharmacist in a crisis response, and to identify potential learning opportunities for a future mass casualty event.Case Summary: Our initial response targeted 3 general areas: staffing, supplies, and communication. Pharmacist and technician staffing was increased throughout the hospital, with a 6-fold increase of pharmacists to the emergency department (ED). To ensure adequate supplies were available, inventory on the ED automatic dispensing cabinets (ADC) was assessed for vaccines, antibiotics, and vasoactive medications. ED pharmacists prepared emergent intravenous medications in the ED while the sterile products room bolstered our supply of intravenous medications for patients in the ED and operating room. Overall, there was a 33% increase in the number of ADC transactions, with pharmacists representing 28% of all ADC transactions. To optimize communication, we formulated a comprehensive plan for the timely dissemination of information to the entire pharmacy staff.Discussion: A mass casualty event is a rare occasion, and it is vital for the pharmacy department to respond rapidly with little notification.Conclusion: The role of a pharmacist is unique and can most effectively triage drug information and medication distribution, especially during times of high demand and high stress.